DETERMINANTS OF ECONOMIC GROWTH INFLUENCED BY CLIMATE CHANGE - Fitya Mukti, Diah Afriani; Setyowati, Eni; Faridatussalam, Sitti Retno (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
Climate change is a major issue since it is intimately linked to economic activities that influence the rate of economic growth. The reason for this research is that climate concerns are worsening and affecting economic sectors all over the world, particularly in Asia (Indonesia, Philippines, Thailand, Japan, and China) and Europe (Norway, Austria, Hungary, Ukraine, and Italy). This is what will have an impact on future economic activity. As a result, it will slow the country's economic growth. Based on this occurrence, researchers wish to know the influence of climate change with indicators of increasing earth temperature, carbon dioxide (ð‘¶ð‘‚ 2), methane (ð‘¶ð‘» 4), and average rainfall on agricultural, fisheries, and forestry sectors simultaneously or separately. The impact of rising global temperatures, CO2 levels, methane levels, and average rainfall on economic growth. The Quantitative Method was utilized in this study, with data obtained from a second party (secondary) in the form of panel data processed using Eviews9 software. This study used the causal step technique, which involves employing mediating factors to construct a regression equation. The causal step technique is based on three regression equations for mediating variables, which can be stated as perfect mediation or partial mediation. Keywords :Economic Growth, Climate Change, Global Warming